2017
DOI: 10.1098/rspb.2017.1925
|View full text |Cite
|
Sign up to set email alerts
|

Culture of an aphid heritable symbiont demonstrates its direct role in defence against parasitoids

Abstract: Heritable symbionts are common in insects with many contributing to host defence. is a facultative, bacterial symbiont of the pea aphid, that provides protection against the endoparasitoid wasp Protection levels vary among strains of that are differentially infected by bacteriophages named APSEs. By contrast, little is known about mechanism(s) of resistance owing to the intractability of host-restricted microbes for functional study. Here, we developed methods for culturing strains of that varied in the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
84
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 54 publications
0
84
1
Order By: Relevance
“…The primary mechanism of resistance against Braconid wasps in the pea aphid, Acyrthosiphon pisum (Harris), has been attributed to the Acyrthosiphon pisum Secondary Endosymbiont (APSE) bacteriophage that is frequently associated with H. defensa (Moran et al, 2005;Degnan & Moran, 2008a,b;Oliver et al, 2009). Phage-derived factors have been reported to arrest the development of wasp embryos (Brandt et al, 2017). By contrast, resistance of the peach-potato aphid, Myzus persicae (Sulzer), to Braconid wasps was associated with the facultative endosymbiont R. insecticola (von Burg et al, 2008;Vorburger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The primary mechanism of resistance against Braconid wasps in the pea aphid, Acyrthosiphon pisum (Harris), has been attributed to the Acyrthosiphon pisum Secondary Endosymbiont (APSE) bacteriophage that is frequently associated with H. defensa (Moran et al, 2005;Degnan & Moran, 2008a,b;Oliver et al, 2009). Phage-derived factors have been reported to arrest the development of wasp embryos (Brandt et al, 2017). By contrast, resistance of the peach-potato aphid, Myzus persicae (Sulzer), to Braconid wasps was associated with the facultative endosymbiont R. insecticola (von Burg et al, 2008;Vorburger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the physical mechanisms and classical innate immune system, there is increasing evidence that insects form intimate partnerships with mutualistic bacteria that protect them against viruses, pathogenic bacteria, parasites, fungi and parasitoids (Bian, Xu, Lu, Xie, & Xi, 2010;Dong, Manfredini, & Dimopoulos, 2009;Flórez, Biedermann, Engl, & Kaltenpoth, 2015;Koch & Schmid-Hempel, 2011;Scarborough, Ferrari, & Godfray, 2005;Teixeira, Ferreira, & Ashburner, 2008). Mechanisms deployed by defensive mutualists for host protection include competing with antagonists for limited host resources (Herren et al, 2014;Paredes, Herren, Schüpfer, & Lemaitre, 2016), production of inhibitory substances such as toxins or antibiotics (Brandt, Chevignon, Oliver, & Strand, 2017;Flórez et al, 2017;Hamilton, Peng, Boulanger, & Perlman, 2015;Kaltenpoth, Göttler, Herzner, & Strohm, 2005;Kroiss et al, 2010), priming or maturation of the host immune system (Emery, Schmidt, & Engel, 2017;Kim et al, 2015;Konrad et al, 2012;Weiss, Maltz, & Aksoy, 2012;Weiss, Wang, & Aksoy, 2011) and improvement of host vigour by modulating nutrient allocation, growth rate or behaviour (Gerardo & Parker, 2014). Additionally, host-symbiont-pathogen interactions can facilitate the evolution of reduced pathogen virulence (Ford, Kao, Williams, & King, 2016;Read, 1994), mitigating detrimental fitness effects on the host.…”
mentioning
confidence: 99%
“…More relevant may be that the protection against parasitoids conferred by H. defensa appears to have a different mechanistic basis than that conferred by R5.15. It is possible that the APSE-encoded factors, presumably toxins (Moran et al, 2005a), that have been shown to be causally involved in H. defensa-mediated disruption of parasitoid development (Brandt et al, 2017), will also cause some 'collateral damage' to the host. This APSE phage is not present in the genome of R. insecticola strain R5.15 (Hansen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%